Collective efficacy and manufacturing schedule instability: a study in Hong Kong and the Pearl River Delta region. (1st December 2008) - Law, Kris M.Y.; Pujawan, Nyoman
Schedule instability has been a major problem in the manufacturing industries. This study is to investigate how the various influencing factors affect the schedule instability experienced by manufacturing companies. A research framework is developed by hypothesising the effect of the key factors (relationships with the supplier and customers, and internal operation) on schedule instability and the correlation between collective efficacy on performance and schedule instability. The results obtained indicate that the internal operations of manufacturing companies and relationships with customers have significant impacts on the degree of collective efficacy perceived, while internal operations are significantly correlated to customer relationships.